Antimicrobial activity of bitespiramycin, a new genetically engineered macrolide. Issue 19 (1st October 2017) - He, Weiqing; Yang, Chunping; Zhao, Xiaofeng; Wang, Yiguang
Graphical abstract: Highlights: We analyzed the in vitro activity of bitespiramycin against common human pathogens. It was compared against that of acetylspiramycin and azithromycin. Bitespiramycin's activity was comparable to azithromycin's. Bitespiramycin's activity was better than that of acetylspiramycin's. Bitespiramycin may be an alternative agent for treating common pathogen infections. Abstract: The antimicrobial activity of bitespiramycin (BT) against Chlamydia trachomatis (Ct), Chlamydia pneumoniae (Cp), Ureaplasma urealyticum (Uu), and Mycoplasma pneumoniae (Mp), was compared with those of azithromycin (AZM) and acetylspiramycin (AT-SP) in vitro . Furthermore, the anti-Mp activities of BT and AZM were evaluated in a hamster model. The activities of BT in vitro were similar to those of AZM but were more effective than those of AT-SP. BT effectively inhibited Mp infection at a dose of 200 mg/kg in a hamster model.